The Instructors’ Perception toward Implementing ICTs in Teaching and Learning Process: A Case Study at Alrefak University in Libya - Enfes, Amani Ismail (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
This research study was conducted to measure the instructors’ perception toward implementing Information and Communication Technologies (ICT) in teaching and learning process: A case study at Alrefak University in Libya based on their gender, age, and field of study in terms of three sub-dimensions; instructors’ perception in ICT use, ICT usage in classroom, and ICT selection criteria. This study employed quantitative research method with the use of survey approach that had a Perception of Teachers on the Usage of ICT scale that was used for data collection tool. 84 participants were reached who agreed to participate voluntarily at Alrefak University in Fall 2020-2021semester. The data was analyzed by using descriptive analysis techniques. Mean (x), Frequency (f), Percentage (%), One-Way ANOVA, and an independent sample T-test were used for analyzing the data. As a result, the study revealed that Alrefak University instructors are positive on ICT integration toward teaching and learning process with no clear difference among males and females. Nevertheless, instructors from educational fields showed high level of perception towards ICT implementations whereas the instructors from business fields showed the lowest level of perception towardsICT implementations. Furthermore, 20- 29 age group of instructors showed the highest level of perception towards ICT implementation when it compared to other age groups. Therefore, both instructors’ ages and Fields of study are considered as major determinant of their perception toward ICT usage in teaching and learning process at Alrefak University in Libya.

ÖZ: Bu araştırmanın temel amacı, öğretim elemanlarının öğretme ve öğrenme sürecinde Bilgi ve İletişim Teknolojilerini (BİT) uygulamaya yönelik algılarını ölçmektir. Çalışma, Libya Alrefak Üniversitesi'nde görev almakta olan öğretim elemanlarının cinsiyet, yaş ve çalışma alanlarına göre üç alt boyutta incelenmesi ile gerçekleştirilen bir durum çalışmasıdır. Ayrıca, bu çalışmada, eğitmenlerin BİT kullanımındaki algısı, sınıfta BİT kullanımı ve BİT seçim kriterlerini de ele alınmıştır. Araştırmada, veri toplama aracı olarak ‘BİT Kullanımına İlişkin Öğretmen Algısı’ ölçeği kullanılmıştır. Araştırma nicel bir araştırma olarak tasarlanmış ve tarama yönteminde gerçekleştirilmiştir. Çalışma grubu, Alrefak Üniversitesi’nin 2020-2021 sonbahar döneminde görev almakta olan öğretim elemanlarından oluşmuştur. Veriler, tanımlayıcı analiz teknikleri kullanılarak analiz edilmiştir. Verilerin analizinde Ortalama (x), Sıklık (f), Yüzdelik (%), Tek Yönlü ANOVA ve bağımsız örneklem T testi kullanılmıştır. Çalışma sonucunda Alrefak Üniversitesi öğretim elemanlarının, kadın ve erkekler arasında net bir fark olmaksızın, öğretme ve öğrenme sürecinde BİT uygulamasına yönelik olumlu bir algıya sahip olduğu ortaya çıkmıştır. Bununla birlikte, eğitim alanlarından öğretim elemanlarının BİT uygulamalarına yönelik yüksek düzeyde algı gösterdiği, işletme alanlarında görev yapan öğretim elemanlarının ise BİT uygulamalarına yönelik en düşük algı düzeyinde olduğu belirlenmiştir. Ek olarak, 20- 29 yaş grubu öğretim elemanlarının, diğer yaş gruplarında olan öğretim elemanlarına göre, BİT uygulamasına yönelik en yüksek algı seviyesine sahip oldukları belirlenmiştir. Bu nedenle hem eğitmenlerin yaşları hem de çalışma alanları, Libya'daki Alrefak Üniversitesi'nde öğretim ve öğrenim sürecinde BİT kullanımına yönelik algılarının ana belirleyicisi olduğu düşünülmektedir.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2021. Supervisor: Prof. Dr. Ersun İşçioğlu.
Keywords: Computer Education and Instructional Technologies Department; Education, Higher--Information Technology (IT); Computer-Assisted Instruction; E-Learning--Instructor's Perception--Alrefak University--Libya; Education - Computer network resources--Educational Technology--Teacher Attitudes; Educational Technology--Educational Media--E-Learning--E-Library; Information Literacy--Computer Literacy--Digital Literacy--University Instructors; Teaching - Computer network resources; Internet in education; Distance Education; Information Technology--Management; ICT, ICT in Teaching and Learning, Perception, Instructor’s Perceptions, Libya